Food Security and Insecurity Analysis in Jambi Province - Yuhelemni (Pusbindiklatren Bappenas, 2021)
This study analyzed food security and insecurity using FSVA (Food Security and Vulnerability Atlas) mapping approach. The FSVA map presents district distribution based on food security and insecurity indicators. Current issues on food security include a drop in production and productivity due to land conversion, low adoption of technology at the farmer level, price fluctuation and ineffective price management, inefficient commerce system, low quality and quantity of public food consumption, failure to implement Diverse, Nutritious, Balanced and Safe Food Consumption Pattern (B2SA). This study aims to determine the vulnerability level of each district and propose countermeasures to reduce its rate. The results of FSVA mapping show that the 139 districts in Jambi could be grouped into the following categories: vulnerable (4 districts), quite vulnerable (18), sufficiently resistant (34), resistant (61), and very resistant (22). No districts fall under very vulnerable categories. Based on the ratio of per capita normative consumption of cereal production, 36 districts (25.90%) are vulnerable to food. Based on the toddler stunting prevalence, 78 districts (56.12%) are vulnerable to food, while based on the indicators of life expectancy, 48 Districts (34.53%) are food vulnerable.